Conventional incision and drainage versus incision and drainage with primary closure in acute abscess: a prospective study - Singh, Amandeep; Singh, Gurdhian; Sidhu, Darshan Singh; Bhalla, Mohit (International Surgery Journal, 2017)
Background: An abscess is a common surgical condition. Abscesses may occur anywhere in the body. Surgical treatment of subcutaneous and soft tissue abscesses includes percutaneous aspiration, incision and drainage without primary closure, incision and drainage with primary closure with drain. The present study was planned to compare conventional method of incision and drainage with incision and drainage with primary closure in cases of acute -abscesses. Methods: A total of 100 patients with acute abscesses were included in the study and randomized into 2 groups with 50 patients in each group. The present study was carried out to compare the conventional method of incision and drainage with incision and drainage with primary closure of the wounds in acute abscesses with regards to wound healing, post- operative pain, duration of hospital stays and recurrence rates. Results: Wound healing was significantly faster in incision and drainage with primary closure (9.18±0.941days) as compared to conventional method of incision and drainage (16.66±1.944 days) [p <0.05]. Mean hospital stay with convention method of incision and drainage was 7.12±0.718 days and with primary closure was 4.0±0.728days (p <0.05). Mean VAS was significantly less in primary closure as compared with conventional method. Decreasing trend in VAS was observed on day 3, day 5 and day 7 (p value 0.000). Recurrence rate of an abscess was seen in 5 cases in conventional method and 2 cases in primary closure (p >0.05). Conclusions: Author have observed a significant difference noted in time taken for wound healing, postoperative pain, hospital stay and recurrence rate between two groups.